A real-time RT-PCR assay for the detection and quantification of grapevine leafroll-associated virus 3 (GLRaV-3) in Vitis vinifera (Vitaceae) and Planococcus ficus (Signoret) (Hemiptera : Pseudococcidae) - Kruger, Kerstin (University of Pretoria, 2013)
Dissertation (MSc (Entomology))--University of Pretoria, 2008.